Study of health care seeking behaviour for illnesses among malnourished children of age 06-59 months in rural and urban areas of Jabalpur district, Madhya Pradesh - Shukla, Nandini; Toppo, Neelam Anupama; Thakur, Aditya; Kasar, Pradeep Kumar; Sharma, Brajesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Even though appropriate medical care seeking could prevent a significant number of child deaths, significant numbers of children die without ever reaching a health facility or due to delays in seeking care.1 This study aimed to compare health seeking behaviour among malnourished children in rural and urban areas. Methods: Cross sectional study carried out in rural and urban areas of Jabalpur district among 1237 children of age group 06-59 months in randomly selected in eight wards and two blocks of Jabalpur District. Where 720 children were from urban wards and 517 from rural villages. Multistage random sampling technique was used for the selection of study subjects. Predesigned questionnaire used to collect data. Results: Out of 720 children of urban area, percentage of acute malnutrition (low weight-for-height) was 136 (18.8%) while in rural area, out of 517 children percentage of acute malnutrition (low weight-for-height) was 102 (19.7%). Out of 136 malnourished children in urban, 32 (23.5%) were having illness while in rural out of 102, 43 (42.1%) were having illness. In rural areas, the mother or primary care giver of the study subjects preferred nearby government hospital (21.9%) the most during illness. While in urban, registered private practitioner (47%) were mostly preferred for consulting during sickness. Still 16.3% of the caregiver in rural area preferred quacks. Conclusions: This shows that the approach of health seeking behaviour is better in urban areas as compared to rural as people still prefer quacks in rural areas.